THE ROLE OF NEURO-LINGUISTIC PROGRAMMING(NLP) IN THE TREATMENT OF DIFFERENT TYPE PHOBIAS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
While about 2- 6 % of people have the specific types of phobia all around the world, this number increases in children’s cases accounting for 3-9%. What is a phobia? Phobia is an irrational, uncontrollable and persistent fear of specific places, objects or situations. There are several reasons to overcome these problems as early as possible, so phobias do not affect different aspects of a person's life. Since phobias can severely adverse one’s social life and mental state, the early signs should not be neglected, especially in children.